2016
DOI: 10.1186/s12939-016-0323-y
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ smoking experiences, family structure, parental smoking and socio-economic status in Ciudad Juárez, Mexico

Abstract: BackgroundCigarette smoking is the leading cause of preventable death worldwide. Tobacco use and secondhand-tobacco smoke (SHS) exposure are classified as a pediatric disease. In Mexico, the prevalence of smoking has decreased among adults but paradoxically increased among adolescents, particularly among young females. This study was designed to determine the association between adolescents’ smoking experiences (smoking behaviors and second hand smoke [SHS] exposure), family structure, parental smoking and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
25
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 45 publications
12
25
1
3
Order By: Relevance
“…In this study, respondents who were from poor family financial conditions were more likely to smoke than were from rich family financial conditions. This finding is consistent with other findings that showed that tobacco use was strongly associated with adolescents living within a low socioeconomic status (SES) (Bird et al 2016; Rosen et al 2014). Adolescents with low SES might have received more negative influence from smoking parents or other household members about smoking and less support for not taking up smoking or in smoking cessation.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, respondents who were from poor family financial conditions were more likely to smoke than were from rich family financial conditions. This finding is consistent with other findings that showed that tobacco use was strongly associated with adolescents living within a low socioeconomic status (SES) (Bird et al 2016; Rosen et al 2014). Adolescents with low SES might have received more negative influence from smoking parents or other household members about smoking and less support for not taking up smoking or in smoking cessation.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is not much in the literature detailing the smoking situation of Hispanic youth in Canada. This is an area that requires further study as evidence from Mexico [31, 32] and the US [9, 11] shows that Hispanic youth are at an increased risk for smoking behaviours, including the use of flavoured tobacco [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Community programs, school and college policies and interventions that encourage tobacco-free environments and lifestyles can reduce smoking rates (U.S. Department of Health and Human Services 2012). Compared with students from low socioeconomic status background, male students with rich family economic background would receive more knowledge about the harm of tobacco using from parents (Bird et al 2016), and those supported measures would prevent their smoking initiation. Previous study found that parents who believed that quitting would benefit their child were more likely to quit smoking (Mahabee-Gittens et al 2014).…”
Section: Discussionmentioning
confidence: 99%